Finite p-groups in which each absolute central automorphism is elementary abelian (MATEMATIKA, 2017)
In this paper we give necessary and sufficient conditions on a p-group G for each absolute central automorphism of G to be elementary abelian. Also we classify the absolute centre of extraspecial p-groups and show that the absolute central automorphisms of these groups are elementary abelian.